PUBLIC PERCEPTION OF SMART PEOPLE BANDUNG CITY TO REALIZE BANDUNG SMART CITY: PUBLIC PERCEPTION OF SMART PEOPLE BANDUNG CITY TO REALIZE BANDUNG SMART CITY - Erza, Osni; Sofyan, Syofriza; Harmaini, Harmaini; Esther, Astrid Maria (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This research aims to examine the perception of the people of Bandung City about Smart People to realize a sustainable Bandung Smart City, by developing 4 Dimensions, namely Education, ICT, Openness, and Creativity. From these 4 dimensions, it is reflected by 8 Smart People indicators which are assessed based on public perception as beneficiaries of policies to make a society a Smart Citizen. Smart People measurement begins by identifying the potential possessed by the city of Bandung, and analyzing what indicators play a big role and need to be improved in each dimension. Then it implies Government policies as a bridge between the community and the Government in making decisions. This study uses the Mixed Method. The data was processed by Structural Equation Modeling, testing based on the Confirmatory Factor Analysis (CFA) theory. To support this quantitative data, the researcher conducted interviews with stakeholders directly involved in the development of Smart People in the city of Bandung. The relevance of this research is very much in accordance with the Faculty Research Road Map referring to Sustainable Development. The results of this study explain that the Information Communication Technology dimension reflects Smart People which has the highest loading standard of 0.94. The Community Openness Indicator is the one that has the lowest loading standard of 0.59, and it is hoped that this indicator will increase its role in representing Smart People in the city of Bandung.